2014
DOI: 10.1038/sj.bdj.2014.552
|View full text |Cite
|
Sign up to set email alerts
|

Halitosis: a new definition and classification

Abstract: This system allows for multiple diagnoses in the same patient, reflecting the multifactorial nature of the complaint. It represents the most accurate model to understand halitosis and forms an efficient and logical basis for clinical management of the complaint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
77
0
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(85 citation statements)
references
References 131 publications
(136 reference statements)
0
77
0
8
Order By: Relevance
“…According to a report by Aydin et al [3], pathologic halitosis has been etiologically classified into five types: oral, airway, gastroesophageal, blood-borne, and pathologic subjective halitosis. Pathologic subjective halitosis (Type 5) is known as a halitosis complaint without objective confirmation by others or by halitometer measurement [3]. That is, the patient believes there is halitosis, but no odor is clinically detectable [4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to a report by Aydin et al [3], pathologic halitosis has been etiologically classified into five types: oral, airway, gastroesophageal, blood-borne, and pathologic subjective halitosis. Pathologic subjective halitosis (Type 5) is known as a halitosis complaint without objective confirmation by others or by halitometer measurement [3]. That is, the patient believes there is halitosis, but no odor is clinically detectable [4].…”
Section: Introductionmentioning
confidence: 99%
“…The former includes obsessive-compulsive spectrum disorder and olfactory reference syndrome; the latter includes several chemosensory disorders such as olfaction and gustation [3]. Most pathologic subjective halitosis complaints are attributed to psychological factors, but at least some are neurological [3]. To date, it has been reported that 75% of olfactory reference syndrome patients present with pathologic subjective halitosis complaints [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both are associated with production of volatile sulfur compounds which may reach the oral cavity by either direct or blood-borne transmission 1 2 4. Where these conditions give rise to breath malodour, treatment has been shown to lead to resolution of halitosis 1 2.…”
Section: Discussionmentioning
confidence: 99%
“…Such substances include volatile sulfur compounds, diamines, indoles and short-chain fatty acids 1 2. Extraoral halitosis may be caused either by the direct passage of similar compounds from the respiratory or gastrointestinal tracts into the mouth, or odorous substances may reach the oral cavity as a result of haematogenous transmission from their site of production and alveolar gas exchange 1 2 4. The gold standard for clinical assessment of halitosis is organoleptic testing, which involves formal assessment of exhaled breath by an experienced examiner to ascertain the presence or absence of malodour.…”
Section: Introductionmentioning
confidence: 99%